Centriole Duplication at the Crossroads of Cell Cycle Control and Oncogenesis - Claude Prigent (Cells)
Centriole duplication is a vital process for cellular organisation and function, underpinning essential activities such as cell division, microtubule organisation and ciliogenesis. This review summarises the latest research on the mechanisms and regulatory pathways that control this process, focusing on important proteins such as polo-like kinase 4 (PLK4), SCL/TAL1 interrupting locus (STIL) and spindle assembly abnormal protein 6 (SAS-6). This study examines the complex steps involved in semi-conservative duplication, from initiation in the G1–S phase to the maturation of centrioles during the cell cycle. Additionally, we will explore the consequences of dysregulated centriole duplication. Dysregulation of this process can lead to centrosome amplification and subsequent chromosomal instability. These factors are implicated in several cancers and developmental disorders. By integrating recent study findings, this review emphasises the importance of centriole duplication in maintaining cellular homeostasis and its potential as a therapeutic target in disease contexts. The presented findings aim to provide a fundamental understanding that may inform future research directions and clinical interventions related to centriole biology.